Acute effect of different interval times between stretching series on hip joint range - Barros, Alexandre Alves dos Santos (2023)
Introduction: flexibility is commonly prescribed in diferents physical activity programs. However, little is known about the most appropriate interval time between sets. Therefore, the aim of this study is to verify the acute effect of diferente intervals between stretching series on the range of motion of the hip. Materials and methods: the study included 72 active men (age between 18 and 40 years, total body mass of 76.84 ±10.88 Kg and height of 1.75 ±0.11 m). The participants were allocated in 4 situations with minimum intervals of 48 hours between them, On the first visit, anthropometric measurements were taken to characterize the sample and on the second, third and fourth visits, the subjects were randomly allocated to each of the three experimental situations (intervals of 30 s., 90 s. and free between series). Results: the results show that the three experimental stretching situations used were able to significantly increase the range of hip abduction when compared with the pre-stretching situation (p=0.00001) and there was significant increase in the joint range of hip abduction in the 30 s. situation in relation to 90 s. (p≤0.03) and free in relation to 90 s. (p≤0.00) after the series of stretching. Conclusion: the intervals of 30 s. and free were more effective than 90 s..